ANALISIS TINGKAT KEPUASAN KONSUMEN TERHADAP KUALITAS PRODUK (STUDI KASUS GOEBOG RESTO, YOGYAKARTA) - Agatha Amalia Rosita; Yitno Purwoko; Andhyka Murti (Journal of Tourism and Economic, 2022)
This study aims to determine the attributes that are priority improvements and to determine the attributes that are considered important by consumers in order to achieve customer satisfaction at Goebog Resto Bantul, Yogyakarta. This research was conducted by collecting data using direct observation and distributing questionnaires to consumers who came and enjoyed the products of Goebog Resto. In this study there are six attributes on product quality which include, food taste, menu variety, dish portions, quality of food ingredients, food presentation, and price. These attributes are used to measure the level of importance and level of performance on product quality. The analysis was carried out using a quantitative descriptive approach with statistical analysis of Importance Performance Analysis (IPA). From the GAP analysis between actual and expected performance, it can be seen that the performance of Goebog Resto Bantul, Yogyakarta has not been optimal beyond what consumers expect.